Crystallography and consequence of the cubic-tetragonal-orthorhombic multi-step martensitic transformations in MnNi alloys. (7th September 2018) - Cui, Shushan; Wan, Jianfeng; Zhang, Jihua; Rong, Yonghua; Chen, Nailu
Abstract: The crystallography of the martensitic transformations (cubic-tetragonal, tetragonal-orthorhombic and cubic-orthorhombic transformations) in MnNi alloys was studied by using the phenomenological crystallography theory of martensitic twinning. The results of habit plane, orientation relationship, macroscopic transformation strain of twinning martensite and angle of shear are obtained. The results show that the rotation angles between martensitic variants and their corresponding Bain variants are smaller than 1°, the angle of shear is smaller than 1° as well. The habit planes slightly deviate from rational {1 1 0}-type planes. Because of relatively small transformation strain and shear angle, the consequence of fcc-fct-fco multi-step transformation in MnNi alloys is mainly determined by transformation thermodynamics, rather than by the resistance of elastic energy.